Removal of chlorides and hardness from contaminated water by using various biosorbents: A comprehensive review - Subhashish Dey; Ganugula Taraka Naga Veerendra; Akula Venkata Phani Manoj; Siva Shanmukha Anjaneya Babu Padavala (Water-Energy Nexus)
A substantial environmental and societal problem is posed by pollutants found in aqueous solution. These pollutants generally consist of dangerous heavy metals and metalloids. In rural locations, hardness and chlorides are among the most dangerous problems of groundwater. Chlorides are regulated in the quality of drinking water because excessive quantities can cause disease. Due to its alkaline nature, both the gaseous and liquid forms of hardness can be irritating to the eyes, respiratory system, and epidermis. The acute biologic effects of hardness and chlorides in humans are dependent on dose and proportionate to their concentration. This includes the amount that is eaten by the body as well as the length of time that the body is exposed to the substance. The naturally occurring physiochemical mechanism known as biosorption is what permits particular biomass to passively concentrate and bind pollutants to its cellular structure. Biosorption can only occur in specific environments. This is a metabolically inert process that does not need any kind of energy, and the quantity of pollutants that a sorbent is able to remove is dependent on its kinetic equilibrium as well as the makeup of its cellular surface. When it came to the biosorption of heavy metals from water, each biosorbent had its own unique set of physical, chemical, and biological features. After the removal of heavy metals, the biosorption process may be made more cost-effective by renewing and reprocessing the biosorbent. This is done after the heavy metals have been removed. In the process of biosorption, many types of bioreactors are used in order to successfully remove the metal ions from huge volumes of water.